Cystathionine β-Synthase Is Necessary for Axis Development in Vivo - Prabhudesai, Shubhangi; Koceja, Chris; Dey, Anindya; Eisa-Beygi, Shahram; Leigh, Noah R.; Bhattacharya, Resham; Mukherjee, Priyabrata; Ramchandran, Ramani (Frontiers in Cell and Developmental Biology, 2018)
The cystathionine ß-synthase (CBS) is a critical enzyme in the transsulfuration pathway and is responsible for the synthesis of cystathionine from serine and homocysteine. Cystathionine is a precursor to amino acid cysteine. CBS is also responsible for generation of hydrogen sulfide (H2S) from cysteine. Mutation in CBS enzyme causes homocysteine levels to rise, and gives rise to a condition called hyperhomocysteinuria. To date, numerous mouse knockout models for CBS enzyme has been generated, which show panoply of defects, reflecting the importance of this enzyme in development. In zebrafish, we and others have identified two orthologs of cbs, which we call cbsa and cbsb. Previous gene knockdown studies in zebrafish have reported a function for cbsb ortholog in maintaining ion homeostasis in developing embryos. However, its role in maintaining H2S homeostasis in embryos is unknown. Here, we have performed RNA analysis in whole zebrafish embryos that showed a wide expression pattern for cbsa and cbsb primarily along the embryonic axis of the developing embryo. Loss-of-function analysis using a combination of approaches which include splice morpholinos and CRISPR/Cas9 genomic engineering show evidence that cbsb ortholog is responsible for anterior-posterior axis development, and cbsa function is redundant. Cbsb loss of function fish embryos show shortened and bent axis, along with less H2S and more homocysteine, effects resulting from loss of Cbsb. Using a chemical biology approach, we rescued the axis defects with betaine, a compound known to reduce homocysteine levels in plasma, and GYY4137, a long term H2S donor. These results collectively argue that cells along the axis of a developing embryo are sensitive to changes in homocysteine and H2S levels, pathways that are controlled by Cbsb, and thus is essential for development.